Livros raros na Universidade de Caxias do Sul: identificação e catalogação descritiva - Rodrigues, Márcia Carvalho (My University, 2014)
It is elaborated, for the first time, the survey and the descriptive cataloging of the collection of rare books of the University of Caxias do Sul with sights to its publicization. The work includes the historical synthesis of the Central Library (BICE/UCS), since its foundation, in 1970. It includes a panorama of the structure and functioning of the BICE/UCS and the System of Libraries of UCS (SIBI/UCS). It examines the concept of bibliographical rarity and the importance of the establishment of criteria of rarity in university libraries. It argues the criteria adopted for the BICE/UCS.
Elabora-se, pela primeira vez, o levantamento e a catalogação descritiva do acervo de livros raros da Universidade de Caxias do Sul com vistas à sua publicização. O trabalho inclui a síntese histórica da Biblioteca Central (BICE/UCS), desde sua fundação, em 1970. Inclui um panorama da estrutura e funcionamento da BICE/UCS e do Sistema de Bibliotecas da UCS (SIBI/UCS). Examina o conceito de raridade bibliográfica e a importância do estabelecimento de critérios de raridade em bibliotecas universitárias. Discute os critérios adotados pela BICE/UCS.
Keywords: Biblioteconomia; Livros raros; Acervos raros; Critérios de raridade bibliográfica; Bibliotecas universitárias; Universidade de Caxias do Sul; Rare books; Rare collections; Criteria of bibliographical rarity; Academic libraries; University of Caxias do Sul; Library science